ENDOGENOUS GROWTH FACTORS IN FOUR CATEGORIES OF COUNTRIES BASED ON HDI - Wasiaturrahma Wasiaturrahma; Nanda Chairunissa (Universitas Riau Kepulauan, 2022)
The economic slowdown is an issue that the global economy still faces since the 2007-2009 Great Recession. The decline in physical and natural capital will further exacerbate this slowdown. This study analyzes the factors driving growth based on endogenous growth theory using a case study of four country categories based on the Human Development Index (HDI) level to solve the economic slowdown problem and realize sustained economic growth as Goal 8 of Sustainable Development Goals (SDGs). The variables used in this study are HDI, Global Innovation Index (GII), labor force, and Gross Fixed Capital Formation (GFCF). This study analyzed 98 countries in 2011-2018 using Fixed Effect and Random Effect Model. The estimation results show that HDI, labor force, GII, and GFCF significantly affect economic growth in the very high, high, and medium HDI country categories. This study found that GII did not affect economic growth in the low HDI countries category.